University Students' Opinions About the Services Given at Student Health Centers - Ebru Öztürk Çopur; Gülümser Kublay (Association of Nurse Managers, 2017)
INTRODUCTION: This study was carried out to determine university students' opinions about the services given at student health centers. METHODS: The study sample included a total of four university student health centers located within the municipality bounders of Ankara Province. The questionnaire form which was developed by the researcher was used as data collection tool. The questionnaire form was applied to students who consulted to each student health center within two weeks (10 working days). The data were collected between September- November 2013.The questionnaire forms consisted of questions about socio-demographic characteristics of participiants, student health centers and services provided in these centers. The analysis of the data was obtained by using descriptive statistical, Ki-kare test analysis methods in SPSS 20.0. RESULTS: According to the study results, 58.06% of the participiants were female, 91.32% of them were unemployed. What sudents like most about student health centers are the speed of services (37,00%), good quality of services (28,78%) and easy access (28,50%). What students dislike about student health services include lack of expert staff (28,90%), limited hours of examination (21,43%) and ack of laboratory services (16,55%). DISCUSSION AND CONCLUSION: In light of these results, it can be recommended to increase the promotion of services given in these health centers, make cooperation and agreement with hospitals and other centers to provide a wider range of services for students and consider the supports and describing expectations of students' to personnels when giving in training and orientation education to increase of service quality and make service planning.